"The Packaging Is Very Inviting and Makes Smokers Feel Like They're More Safe": The Meanings of Natural American Spirit Cigarette Pack Design to Adult Smokers. (April 2019) - Epperson, Anna E.; Averett, Paige E.; Blanchflower, Tiffany; Gregory, Kyle R.; Lee, Joseph G. L.
Background/Aims . The aim of this investigation was to identify which design elements on Natural American Spirit packs are salient to (i.e., noticed by) U.S. adult smokers and what meanings smokers derive from these elements. Method . We conducted a secondary analysis of qualitative data from a study of cigarette packaging design. U.S. adult smokers ( n = 33) from all nine census regions participated in six telephone-based focus groups in March 2017. We used constant comparison analysis to identify key themes. Results . Four themes were identified, two focused on salient design elements and two focused on design element meanings. The themes of "bright and flashy color" and "the American Indian logo" were identified as key design elements, while the themes of "healthy and safer" and "targeting at-risk smokers" were identified as meanings smokers derived from design elements. Conclusions . Pack design elements influence smokers' perceptions about reduced health risk of Natural American Spirit cigarettes and may be especially dangerous to vulnerable populations, including young adults and American Indians. Findings from this study suggest that the banning of text descriptors may not be enough to address misconceptions about "healthier" cigarettes.